Tick-borne rickettsioses, neglected emerging diseases in rural Senegal. - Oleg Mediannikov; Georges Diatta; Florence Fenollar; Cheikh Sokhna; Jean-François Trape; Didier Raoult (Public Library of Science (PLoS), 2010)
BACKGROUND: Rickettsioses are one of the most important causes of systemic febrile illness among travelers from developed countries, but little is known about their incidence in indigenous populations, especially in West Africa. METHODOLOGY/PRINCIPAL FINDINGS: Overall seroprevalence evaluated by immunofluorescence using six rickettsial antigens (spotted fever and typhus group) in rural populations of two villages of the Sine-Saloum region of Senegal was found to be 21.4% and 51% for spotted fever group rickettsiae for Dielmo and Ndiop villages, respectively. We investigated the role of tick-borne rickettsiae as the cause of acute non-malarial febrile diseases in the same villages. The incidence of rickettsial DNA in 204 blood samples from 134 (62M and 72F) febrile patients negative for malaria was studied. DNA extracted from whole blood was tested by two qPCR systems. Rickettsial DNA was found in nine patients, eight with Rickettsia felis (separately reported). For the first time in West Africa, Rickettsia conorii was diagnosed in one patient. We also tested 2,767 Ixodid ticks collected in two regions of Senegal (Niakhar and Sine-Saloum) from domestic animals (cows, sheep, goats, donkeys and horses) by qPCR and identified five different pathogenic rickettsiae. We found the following: Rickettsia aeschlimannii in Hyalomma marginatum rufipes (51.3% and 44.8% in Niakhar and Sine-Saloum region, respectively), in Hyalomma truncatum (6% and 6.8%) and in Rhipicephalus evertsi evertsi (0.5%, only in Niakhar); R. c. conorii in Rh. e. evertsi (0.4%, only in Sine-Saloum); Rickettsia massiliae in Rhipicephalus guilhoni (22.4%, only in Niakhar); Rickettsia sibirica mongolitimonae in Hyalomma truncatum (13.5%, only in Sine-Saloum); and Rickettsia africae in Rhipicephalus evertsi evertsi (0.7% and 0.4% in Niakhar and Sine-Saloum region, respectively) as well as in Rhipicephalus annulatus (20%, only in Sine-Saloum). We isolated two rickettsial strains from H. truncatum: R. s. mongolitimonae and R. aeschlimannii. CONCLUSIONS/SIGNIFICANCE: We believe that together with our previous data on the high prevalence of R. africae in Amblyomma ticks and R. felis infection in patients, the presented results on the distribution of pathogenic rickettsiae in ticks and the first R. conorii case in West Africa show that the rural population of Senegal is at risk for other tick-borne rickettsioses, which are significant causes of febrile disease in this area.